Dk {1−x≥02x−1≥0 ⇒ X∈ [12,1]PT ⇔ 2√1−x+3√2x−1=7x+6√(1−x)(2x−1 -4DẶt t=2√1−x+3√2x−1 ⇔ t2=4(1-x)+9(2x-1)+12√(1−x)(2x−1)⇔ t2=14x-5+12√(1−x)(2x−1) ⇔ t2+5=2(7x+6 √(1−x)(2x−1))⇒ t2++52=7x+6√(1−x)(2x−1)PT ban đầu trở thành t=t2+52 - 4 ⇔ t2 -2t -13 =0 ⇒ t=3 và t=-1với t=3 ⇒ 2√1−x +3√2x−1=3 ⇒ x= 1(tm)tương tự vơi t=-1 ⇒ x=37(l)đúng thì tích v vote up nka mn.....!!!!!!!!!!!!!!!!
Dk
{1−x≥02x−1≥0 ⇒ X
∈ [12,1]PT
⇔ 2
√1−x+3
√2x−1=7x+6
√(1−x)(2x−1 -4DẶt t=2
√1−x+3
√2x−1 ⇔ t2=4(1-x)+9(2x-1)+12
√(1−x)(2x−1)⇔ t2=14x-5+12
√(1−x)(2x−1) ⇔ t2+5=2(7x+6
√(1−x)(2x−1))
⇒ t2++52=7x+6
√(1−x)(2x−1)PT ban đầu trở thành t=
t2+52 - 4
⇔ t2 -2t -3 =0
⇒ t=3 và t=-1với t=3
⇒ 2
√1−x +3
√2x−1=3
⇒ x= 1(tm)tương tự vơi t=-1
⇒ x=
37(l)đúng thì tích v vote up nka mn.....!!!!!!!!!!!!!!!!